A Semantic Analysis of Referential and Contextual Meaning in the Song Lose You to Love Me by Selena Gomez - Thamrin Daulat Dorianus Simanjuntak; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze referential and contextual meanings in the song Lose You to Love Me performed by Selena Gomez. This research employs a qualitative descriptive method to examine how meaning is constructed within song lyrics. Referential meaning refers to the direct relationship between words and real-world entities, while contextual meaning is influenced by emotional, situational, and experiential factors. The data were collected from the official lyrics of the song and analyzed using semantic theories proposed by George Yule and Geoffrey Leech. The findings indicate that contextual meaning is more dominant than referential meaning. Many expressions in the lyrics are metaphorical and reflect emotional experiences such as heartbreak, self-reflection, and personal growth. The study concludes that understanding song lyrics requires contextual interpretation beyond literal meaning.